(untitled) (Scientific journal of the Fergana State University, 2024)
Concepts such as analytical thinking, operations of analysis and synthesis, concretization, abstraction, classification, systematization, individual, neuropedagogy, their essence and structural structure are studied in the article. The stages of development of analytical thinking are analyzed.